La pensión de alimentos dispuesta desde la presentación de la demanda vulnera el debido proceso - Nantipia Velecela, Franz Gabriel (2016)
In this research work broached the subject regarding the maintenance payments arranged from the filing of the application violates due process, making a detailed analysis of rights violations being committed not considered as provided by law and constitutional rights as it is the indispensable participation of the defendant in order that he may also exercise their right to defense, so in practice and reality, for various reasons, the plaintiff or justice operators have left after a specified time before to practice the summons to the defendant, which has caused liquidations alimony are bulky, and carting consequences for the defendant as personal urgency, thus reaching violate due process and therefore the right to defense in an opportune moment. The Constitution of the Republic of Ecuador as guarantor legal body of rights clearly states that in any process in which rights and obligations of any order is determined, the law will ensure due process, and within this legal provision, there are fundamental guarantees as that everyone has the right to defense, with the adequate time and facilities to prepare his defense, to be heard at the appropriate procedural moment and on equal terms; being so inexcusable rights violations, legal provisions are violated against the defendant. If the defendant does not pay two or more pensions of food, and these are calculated from the filing of the application, would lead to the defendant, not knowing of the action, its obligations to accumulate, and that economic problem as there pensions Late unpayable, as later the plaintiff may request personal urgency, as will reflect the Art. 137 of the Code General Process, prior finding by certifying the respective financial institution or non-payment have personal pressure up thirty days and the ban on leaving the country. Consequently all the tools are adjusted in favor of the plaintiff, leaving in full and total defenselessness the defendant, which would be viable food pensions are due from the subpoena to demand and self-acceptance for processing.